Feasibility Analysis of CareToy-Revised Early Intervention in Infants at High Risk for Cerebral Palsy - Beani, Elena; Menici, Valentina; Cecchi, Alessandra; Cioni, Maria Luce; Giampietri, Matteo; Rizzi, Riccardo; Sgandurra, Giuseppina; Cioni, Giovanni; , CareToy-R Consortium; Artese, Claudia; Barzacchi, Veronica; Cervo, Marta; et al. (Frontiers in Neurology, 2020)
Infants with perinatal brain injury are at high risk for Cerebral Palsy (CP). Progresses in detection of early signs of brain injury and of CP allow early intervention (EI) programs for improving the outcome of these infants. CareToy system (CT), developed within a European project (Trial Registration: NCT01990183), allows providing, by means of tele-rehabilitation, a highly personalized, family-centered, home-based EI for young infants, remotely managed by clinicians. CareToy, already used with pre-terms without brain injury, has been adapted for high-risk infants in a project funded by the Italian Ministry of Health, and the CareToy-Revised (CareToy-R) has been realized (Trial registration: NCT03211533 and NCT03234959). Before assessing its efficacy, it was crucial to evaluate the acceptability, usability, and feasibility of CareToy-R EI. Nineteen high-risk infants with perinatal brain injury, aged 5.95 ± 2.13 months (range 3.12–10.78 months), carried out an 8-week training with CareToy-R at home, performing customized playful activities with their parents, tailored to their rehabilitative needs, remotely managed by clinicians. The feasibility of training and study procedures was assessed through criteria derived from literature; acceptability and usability have been analyzed from data about individual training and an ad hoc questionnaire. All CareToy-R trainings were planned by the clinical staff with a daily personalized use for each infant between 30 and 45 min (mean 34.37 min). The amount of executed training by the infants was very high (daily mean 30.30 min), with no differences related to infant age, sex, and gestational age. All the nine feasibility criteria were achieved, family compliance to the project was very good, data collection was completed and the CareToy-R system worked properly and easily for parents. The answers to the questionnaire had a total mean score of 84.49% and they ranged from a minimum of 81.05% (in “easy to use” area) to a maximum of 86.49% (“changes due to the training” area), with no differences related to nationality or familiarity with technology of the mothers. This study reports preliminary evidence to the feasibility of a home-based EI with CareToy-R system in infants at high risk for CP. Results of the RCT will provide data about the potential effectiveness of this approach.